Using Trusted Sensors to Monitor Patients' Habits - Wolman, Alec; Saroiu, Stefan; Bahl, Paramvir; Bahl, Victor (1st USENIX Workshop on Health Security and Privacy (HealthSec), 2010)
Patients are notoriously inconsistent with taking their medications. Doctors and insurance companies have an incentive to monitor and collect data on whether medical patients and insurance customers are following prescriptions and maintaining a healthy lifestyle. A convenient way of gathering such data is using smartphones. For example, accelerometer readings can be used to reveal how physically active a patient is. Unfortunately, the readings of a sensor can be easily manipulated. This data’s huge financial value makes doctors and insurance companies reluctant to use it unless it can be made more trustworthy. This paper’s goal is to start a discussion on how to use trusted sensors to help doctors and insurance companies gather data about their patients ’ medications in a trustworthy manner.